MST561 - Statistical Inference February 2021 - PPSM, Pusat Pengajian Sains Matematik (Pusat Pengajian Sains Matematik, 2021)
Please check that this examination paper consists of FIVE (5) pages of printed material before you begin the examination. Instructions : Answer ALL FIVE (5) questions.